2018
DOI: 10.5152/tud.2018.73669
|View full text |Cite
|
Sign up to set email alerts
|

The frequencies of Y chromosome microdeletions in infertile males

Abstract: Y chromosome microdeletions were detected quite frequently in certain infertility subgroups. Therefore, detailed evaluation of an infertile man by physical examination, semen analysis, hormonal evaluations and when required, karyotype analysis may predict the patients for whom Y chromosome microdeletion analysis is necessary and also prevent cost increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
(23 reference statements)
1
12
0
1
Order By: Relevance
“…Among the 717 patients with azoospermia in the present study, AZFa, AZFb, AZFc, AZFb+c, and AZFa+b+c deletions were observed in 0.6%, 0.6%, 3.9%, 1.3%, and 1.1% of the patients, respectively, which were similar to those reported in previous studies. 6 7 8 9 10 In patients with severe oligozoospermia, the AZFc deletion was observed in 8.0% of patients, which was higher than that in patients with azoospermia. To detect AZFc deletions, the EAA/European Molecular Quality Network (EMQN) guidelines 1 recommended Y chromosome microdeletion screening at a sperm count of <5 × 10 6 ml −1 , whereas Johnson et al .…”
Section: Discussionmentioning
confidence: 94%
“…Among the 717 patients with azoospermia in the present study, AZFa, AZFb, AZFc, AZFb+c, and AZFa+b+c deletions were observed in 0.6%, 0.6%, 3.9%, 1.3%, and 1.1% of the patients, respectively, which were similar to those reported in previous studies. 6 7 8 9 10 In patients with severe oligozoospermia, the AZFc deletion was observed in 8.0% of patients, which was higher than that in patients with azoospermia. To detect AZFc deletions, the EAA/European Molecular Quality Network (EMQN) guidelines 1 recommended Y chromosome microdeletion screening at a sperm count of <5 × 10 6 ml −1 , whereas Johnson et al .…”
Section: Discussionmentioning
confidence: 94%
“…Approximately 15% of couples worldwide are unable to conceive due to infertility and males contribute to 50% of the infertility cases 20,21 . There are several causative factors for male infertility, including genetic and environmental factors [21][22][23][24] . Abnormal semen (dysspermatism) is a reason for infertility, which occurs in about 50% of the cases of male infertity 25,26 .…”
mentioning
confidence: 99%
“…Using a higher sensitivity technique leads to increase in detection limit of Y microdeletions which explains the difference between our results and previous studies that reported a lower incidence of microdeletions due to using PCR technique detecting 6 STS [22], 10 STS [26] Fourty seven percent of Y microdeletions in our study were detected in the AZFb+c, Thirty eight percent of microdeletions were identified in AZF-c patients, 9.5% in AZF-a+b+c and only 4.8%in AZF-b. Our data are showed that the highest incidence in Y microdeletions was in AZF-b+c; most of international reports revealed that, deletions of AZFc were at highest frequency Deletions in AZFc region was the most frequent 75% [27], (48.1%) [28], (46.6 %) [29].Variation in the reported frequencies could be related to the difference in ethnicity and sample size variability. In our study, among 114 azoospermic patients, 21/114 (18.4%) had detectable Y chromosome microdeletions vs. only 3/36 patients (8.3%) in the oligospermic group.…”
Section: Discussionmentioning
confidence: 58%